Increasing the competitiveness of Kazakhstan's economy through the development of clusters . (Journal of Economic Research & Business Administration, 2015)
In today's highly competitive markets of industrial goods and the achievements of science changes the direction of economic development and industrial organization . Sustaining a competitive national economy is a priority. Its implementation is possible through the introduction of advanced technology , environmentally friendly , safe production , quality management systems, products, systems, resource , etc.
Keywords: competitiveness of the economy